Evolución del sistema financiero en la región Loreto, periodo 2013 – 2022 - Barrera Mori, Kimberly Alicia (2025)
The main objective of this research was to analyze the evolution of the financial system in the Loreto region during the 2013-2022 period, evaluating the behavior of direct credits, deposits, and financial assets. A quantitative approach was used, with the study being descriptive in scope and employing a non-experimental, longitudinal design. The data were collected using the documentary observation technique from the Financial System, supervised by the Superintendence of Banking, Insurance, and AFP. The most important results show a significant growth in direct credits by 59.1%. Likewise, total deposits increased by 84%, with Multiple Banks contributing the most. Financial assets also showed positive growth, with a higher concentration in banks, which accounted for more than 80% of the total. The conclusions indicate a favorable evolution of the financial system in Loreto, mainly driven by the sustained growth of Multiple Banks. However, significant fluctuations were observed during the COVID-19 pandemic, temporarily affecting the behavior of credits and deposits. This study provides a comprehensive view of the financial behavior in the Loreto region and highlights the importance of banks in offering credit and attracting deposits, contributing to the stability of the local financial system.